The massive Elko spinor field in the de Sitter braneworld model - M Moazzen Sorkhi; A Tofighi; Z ghalenovi (Iranian Journal of Physics Research, 2019)
The Elko spinor field is a spin 1/2 fermionic quantum field with a mass dimension introduced as a candidate of dark matter. In this work, we study the localization of Elko fields on a de Sitter thick brane constructed by a canonical or phantom scalar field. By presenting the mass-independent potentials of Kaluza-Klein (KK) modes in the corresponding Schrödinger equations, it is shown that the Elko spinor field with a five- dimensional mass term can be localized on de Sitter branes. Also, by using a Yukawa type coupling term, we find that the Elko spinor field can be localized on this brane with a particular coupling constant. Furthermore, it is shown that the zero mode of the  Elko field is localized on the de Sitter brane through a Yukawa geometrical coupling term.